Individual and contextual influences on the affective commitment of retail salespeople - Simintiras, Antonis; Watkins, Alan; Ifie, Kemefasu; Georgakas, Konstantinos (Journal of marketing management, 2012)
Salesperson characteristics as well as managerial approaches have been found to play an important role in the development of positive attitudes by salespersons towards an organisation. This study integrates these two research areas to investigate the personal and contextual antecedents of affective organisational commitment of retail salespeople. Fit theory and the literature on person-situation interaction provide the theoretical bases for explaining how salesperson selling skills, job liking, and empowerment individually and jointly influence affective commitment. A multilevel modelling approach is used to analyse data from 105 sales managers and 419 salespeople. Findings reveal that salespersons' affective commitment is influenced by their selling skills, degree of job liking, tenure, and empowerment. The results also indicate that the impact of selling skills on affective commitment is higher when empowerment is high. Based on the study's findings, implications for managing salespeople as well as limitations and suggestions for future research are offered.